Pengembangan potensi budidaya lidi sawit di Desa Tualang Timur Kabupaten Siak dalam sektor industri - Ratu Dahlia; Lara Dwi Mei Yendra; Muhammad Adri Irfandri; Putri Rahmadani; Ikhwanul Khairy; Praduta Zaky; Dini Anis Monika; Sindi Ela Wahyu Lestari; Sindi Arnelia; Muhammad Nanda Miftahul Jannah; Indra Lesmana (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
This study aims to analyze the potential development of palm oil cultivation in Tualang Timur Village, Siak Regency in the industrial sector. Various kinds of suitable solutions from various inhibiting factors for business development are also the targets of this research. The complete sequence of the process of making palm sticks from collecting materials to the weaving process will also be described in this study where the researchers participate directly in the manufacturing process. This study uses qualitative research methods and data collection methods in the form of field observations, interview activity and training with one of the residents, namely bu Desi as one of the residents who manages the cultivation of oil palm sticks. Researchers will also describe of how the business development system looks like through marketing and distribution of handicraft business products. The importance of the involvement of researchers in the processing of palm oil sticks is the main benchmark in the success of the research. The conclusion of this study is that Tualang Timur Village has a superior product, namely palm sticks which can be a potential progress of the village area in the field of business and cultivation.